GENESIS OF HOLDINGS AND AGROHOLDINGS IN UKRAINE AS AN INSTITUTIONAL UNITS - Белова, І. М.; Завитій, О. П.; Семенишена, Н. В. (Podilian Bulletin: Agriculture, Engineering, Economics, 2019)
The history of holdings is thoroughly studied in economic and legal science, however, scientists have different views on the place and time of the emergence of these institutional units. The insufficiency of the study of the concept of holdings negatively affects both the holdings themselves and the participants of the economic relations that interact with them, therefore, the identified question requires specificity, which confirms the relevance and purpose of the study of the above-mentioned topic. Despite the spread of holding activities in the agricultural sector of Ukraine, the legislative field lacks a clear interpretation of the concept of holding and, in particular, agricultural holding. Problem-chronological, comparative-historical and statistical methods analyze the question regarding the definition of the concept of holding, by studying the historical background of its occurrence and identifying characteristic features and signs. The necessity of legal regulation and significant improvement of the mechanism of economic relations in which holdings participate, as well as the search for ways to effectively regulate the activities of holdings, are substantiated. Prospects for the effective functioning of holding structures in Ukraine are associated with the need to solve a number of problems. In particular, studies require mechanisms for the official establishment of a holding structure in Ukraine and foreign countries with developed market economies, trends in the development of this form of integration formation and its role in attracting foreign investment for the development of the country's economic potential, and the specifics of financial management of the holding structure